1982
DOI: 10.1161/01.res.51.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Potential fields generated by oblique dipole layers modeling excitation wavefronts in the anisotropic myocardium. Comparison with potential fields elicited by paced dog hearts in a volume conductor.

Abstract: The potential distribution in a homogeneous, cylindrical volume conductor surrounding an isolated paced dog heart was first measured and then calculated by using a mathematical model that stimulates an anisotropic excitation wavefront spreading through the heart muscle. The study was performed with a view to establish to what extent the anisotropy of cardiac generators affects the potential field in the extra-cardiac conducting media at a great distance from the heart. The model considers an oblique dipole lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Moreover these experimental data indicated a strong influence of the myocardial fiber direction on the extracellular and extracardiac potential field and suggested the need of incorporating the anisotropy of the myocardial structure in the macroscopic source models. We remark that, while it has not yet been conclusively shown that the anisotropy of the cardiac muscle has a significant effect on the BSM or BSE, however anisotropy does affect measured potentials in the cardiac muscle and the effects are shown to be of non local character, see [12]. Hence it is believed that in many situations anisotropy is relevant to the understanding of the BSM's and the BSE's.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover these experimental data indicated a strong influence of the myocardial fiber direction on the extracellular and extracardiac potential field and suggested the need of incorporating the anisotropy of the myocardial structure in the macroscopic source models. We remark that, while it has not yet been conclusively shown that the anisotropy of the cardiac muscle has a significant effect on the BSM or BSE, however anisotropy does affect measured potentials in the cardiac muscle and the effects are shown to be of non local character, see [12]. Hence it is believed that in many situations anisotropy is relevant to the understanding of the BSM's and the BSE's.…”
Section: Introductionmentioning
confidence: 88%
“…For general references to the theory of such syncytia of electrically coupled media and its applications to cardiac tissues, see, e.g., [6,8,12,14,30,46,58,59,61]. The bidomain model is a macroscopic one, suitable for the far-field simulations required in the EFP.…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure of the heart muscle is far too complicated to permit a realistic theoretical estimate of the anisotropy, its influence on the wavefronts has been studied, e.g. COLLI-FRANZONE et al (1982), GONELLI and AGNELLO, (1988).…”
Section: Ifmbe: 1988mentioning
confidence: 99%
“…The direction of the straight line joining the two maxima correlated well with the direction of subepicardial muscle fibers near the pacing site.1-6 This finding is consistent with the "oblique dipole layer" model of the excitation wavefront. 7 The model assigns greater dipole strength per unit area to the portions of a wavefront that propagate along fibers (axial component) than to those that propagate across fibers. The model also predicts that, in the experimental conditions specified above, positive potentials will be generated only in those areas toward which the wavefront is spreading along fibers.8…”
mentioning
confidence: 99%